The evolution of human endurance. Research on the biology of extreme endurance gives insights into its evolution in humans and animals - Hunter, P. (EMBO reports, 2019)
Theoretische Betrachtungen zur Entwicklung von Ausdauerleistungen bei Mensch und Tier.